THE IMPORTANCE OF PEDAGOGICAL TECHNOLOGIES IN THE IMPLEMENTATION OF INNOVATIVE PEDAGOGICAL ACTIVITIES OF A MATHEMATICS TEACHER - Raxmonov Istam Yarikulovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this article discusses the possibility of using pedagogical technologies in the implementation of innovative pedagogical activities of the mathematics teacher.